EMPOWERING MADRASAH TEACHERS IN MOJOKERTO THROUGH AI-BASED APPLICATIONS: ENHANCING TEACHING COMPETENCE AND CLASSROOM ENGAGEMENT - Anggrisia, Nur Fitria; Basori, Basori; Mubarok, Harir; Degaf, Agwin (Fakultas Sains dan Teknologi, 2024)
This community service program aimed to enhance the understanding and skills of madrasah teachers in Mojokerto in utilizing Artificial Intelligence (AI) applications for teaching and learning activities. A total of 70 teachers participated in the program, which applied the ASSURE instructional model. The program involved interviews and pre-training questionnaires to assess the challenges faced by participants related to AI integration in education. The training included workshops, one-on-one coaching, and microteaching, focusing on the use of AI tools such as ChatGPT, Grammarly, and other AI-based learning applications. Post-training evaluations showed a significant increase in teachers' confidence and competence in using AI-based applications, with participants expressing enthusiasm for integrating these technologies into their teaching to enhance student engagement. The program demonstrated that a hands-on approach is effective in improving teachers' technological skills and motivation to use AI in their teaching practices. Continued professional development and support will be crucial to sustain these improvements and further strengthen the integration of AI in madrasah education.